Studi Pemanfaatan Lumpur Limbah Cair B-3 yang Mengandung Pb dan Cr dari Industri Percetakan sebagai Bahan Baku Tambahan Pembuatan Paving Block (Studi Kasus PT Gramedia Group, Jakarta) - Widiastuti HN; Badrus Zaman; Nita Anggraeni (MEDIA KOMUNIKASI TEKNIK SIPIL, 2012)
Printing industrial wastewater represented hazardous waste. Processing of printing industrial wastewater still yielded by sludge which needing furthermore processing, because it contained heavy metal Pb and Cr, which also had the character of B-3, as does its wastewater. Processing of hazardous waste with solidification process represented the way of processing as efficient and effective alternative and also profit in expense of to the printing industry and to continuity of environment. Sludge could be use as aggregate, which was the raw material in making of block pavement with sand, cement, and water. Research of sludge exploited as an addition of paving block had the character of experimental made block pavement by varied 10%, 15%, 20%, 25%, 30%, 35%, 40% sludge in sand. Results indicated that with substitution until 30 % of sludge weight replacing sand as aggregate in the reality could yielded block pavement powerfully depress fulfilling SNI 03-0691-1996. The highest strength depress was yielded by addition 10% of sludge powerfully depress 229.375 kg / cm2 and was absorption of water 11.334%. Leaching test with submerged simulation gave result that concentration of Pb and Cr still below standard quality of hazardous waste that was 0,1ppm and 0,5 ppm and was leaching rate of pavement block downhill progressively by increasing day it of submerged. Result of this research was expected could become alternative processing of hazardous waste and advantaging in expense. Keywords: sludge, hazardous waste, solidification, block pavementPermalink: http://ejournal.undip.ac.id/index.php/mkts/article/view/3911[How to cite: Widiastuti HN, Zaman, B. dan Anggraeni, N., 2005, Studi Pemanfaatan Lumpur Limbah Cair B-3 yang Mengandung Pb dan Cr dari Industri Percetakan sebagai Bahan Baku Tambahan Pembuatan Paving Block (Studi Kasus PT Gramedia Group, Jakarta), Jurnal Media Komunikasi Teknik Sipil, Volume 13, Nomor 2, pp. 75-8]